The Correlation Between Self Efficacy and Reading Comprehension Ability at the Tenth Grade Students’ SMAN 8 Tanjabtim - Saputra, Deki; Aruan, Rumiri Rotua; Masyhur, Masyhur (CV. Rayyan Dwi Bharata, 2025)
The purpose of this research is to determine the relationship between self-efficacy and reading comprehension. This research uses correlational research with a quantitative design. The sample was 30 class E2 students at SMAN 8 Tanjung Jabung Timur. Data collection was carried out using two instruments: (1) a self-efficacy questionnaire which was used to measure students' reading self-efficacy and (2) a reading comprehension test which was used to determine students' reading comprehension. The correlation of the two variables is calculated using Pearson Product Moment in SPSS 15. The results show that the correlation coefficient has a value between 0.20 and 0.40, then the two variables have a low level of correlation. Therefore, the alternative hypothesis (Ha) is rejected and it can be stated that there is no significant correlation between Self Efficacy and Reading Comprehension Ability of the tenth grade students' SMA N 8 Tanjung Jabung Timur. The coefficient of determination is 0.0723, indicating that the self efficacy has a 7.23% influence on students' reading comprehension ability, while the remaining 93% is caused by other factors.